Randomised controlled trial of Alexander technique lessons, exercise, and massage (ATEAM) for chronic and recurrent back pain: economic evaluation. (11th December 2008) - Hollinghurst, Sandra; Sharp, Debbie; Ballard, Kathleen; Barnett, Jane; Beattie, Angela; Evans, Maggie; Lewith, George; Middleton, Karen; Oxford, Frances; Webley, Fran; Little, Paul
Abstract : Objective An economic evaluation of therapeutic massage, exercise, and lessons in the Alexander technique for treating persistent back pain. Design Cost consequences study and cost effectiveness analysis at 12 month follow-up of a factorial randomised controlled trial. Participants 579 patients with chronic or recurrent low back pain recruited from primary care. Interventions Normal care (control), massage, and six or 24 lessons in the Alexander technique. Half of each group were randomised to a prescription for exercise from a doctor plus behavioural counselling from a nurse. Main outcome measures Costs to the NHS and to participants. Comparison of costs with Roland-Morris disability score (number of activities impaired by pain), days in pain, and quality adjusted life years (QALYs). Comparison of NHS costs with QALY gain, using incremental cost effectiveness ratios and cost effectiveness acceptability curves. Results Intervention costs ranged from £30 for exercise prescription to £596 for 24 lessons in Alexander technique plus exercise. Cost of health services ranged from £50 for 24 lessons in Alexander technique to £124 for exercise. Incremental cost effectiveness analysis of single therapies showed that exercise offered best value (£61 per point on disability score, £9 per additional pain-free day, £2847 per QALY gain). For two-stage therapy, six lessons in Alexander technique combined with exercise was the best value (additional £64 per point on disability score, £43 per additional pain-free day, £5332 per QALY gain). Conclusions An exercise prescription and six lessons in Alexander technique alone were both more than 85% likely to be cost effective at values above £20 000 per QALY, but the Alexander technique performed better than exercise on the full range of outcomes. A combination of six lessons in Alexander technique lessons followed by exercise was the most effective and cost effective option. How does the Alexander Technique work? What are the authors findings about the clinical and cost effectiveness of the treatment? Watch this video to find out (12 mins). media-1 10.1136/bmj.a2656V1